(untitled) (Indian Journal of Arid Horticulture, 2025)
This study investigates the morphological diversity among 38 date palm genotypes grown in Kachchh, India, using Principal Component Analysis (PCA) and Hierarchical Clustering. A dataset comprising 27 quantitative and qualitative traits were analysed. The correlation analysis revealed significant associations between key traits such as pulp thickness, fruit weight, and pulp-to-stone ratio, which are crucial for fruit quality improvement. PCA identified major traits contributing to morphological variability, with the first three principal components explaining over 52% of total variance. Hierarchical clustering grouped genotypes into four distinct clusters, demonstrating significant genetic diversity. The findings highlight the importance of fruit-related traits in genetic differentiation and provide a framework for breeding superior date palm genotypes.